Pendampingan Laporan Keuangan Sekolah Dasar Berbasis Microsoft Excel: Financial Reporting Assistance Elementary School Based on Microsoft Excel - Biduri, Sarwenda; Fauziyah, Luluk Putri; Hanif, Aisha (Antis-publisher, 2024)
Primary school financial reports are an important instrument in presenting financial information to stakeholders. The purpose of this activity is to achieve transparency and accountability in the presentation of school financial reports. In an effort to improve the transparency and accountability of school financial management, mentoring is carried out in stages involving the school principal, school treasurer, and the abdimas team. Data collection methods involved observation, situation analysis, as well as socialisation of the importance of financial reports for organisations. The results showed that the preparation of computer-based financial reports using Microsoft Excel can facilitate data input and online integration. With structured financial reports, schools can ensure transparency in the use of funds and fulfil responsibilities to internal and external parties.